Name reaction, rearrangement and mechanism : Problem solving approach - Jena, Satyaban; Rout, Laxmidhar (New Delhi: Indu Book services, 2024)
There are seven chapters in the book starting from scratch to complex level. Chapter 1 is started with problems on carbonation based name reaction and rearrangement including complete mechanism. Chapter 2 deals with name reaction and rearrangement of carbanion intermediate. Chapter 3 covers radical based name reaction and rearrangement including radical cation and radical anions. Chapter 4 is related to name reaction and rearrangement and mechanism of carbene based intermediates including nitrene, ketene and isocyanate. Chapter 5 is related to problems miscellaneous name reaction and rearrangement not covered in earlier chapters, whereas Chapter 6 contain very important fragmentation based name reaction and mechanism. Chapter 7 contains road map problems based on name reaction and rearrangement. This final chapter is designed based on the knowledge of all previous chapters.
Includes appendix
Keywords: Organic reactions -- Reaction mechanisms (Chemistry) -- Molecular rearrangements